การศึกษาการรับน้ำหนักบรรทุกปลอดภัยและอายุการใช้งานของโครงสร้างสะพานแบบแผ่นพื้น - กิตติ จิวโพธิ์เจริญ (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
To study the safe load carrying capacity and the service life of the bridges. The slab-type reinforced concrete bridges having the span length from 5 to 10 meters are considered since they are the most popular bridge type used in Thailand. To accurately evaluate the safe load carrying capacity and the service life, the related field data from the actual bridge are collected. The Bridge WIM system is installed in a test bridge to monitor the actual traffic data. Two test trucks running on the bridge with various speed and conditions are employed to perform the system calibration. By comparing with the nearby weight station, the installed B-WIM system can provide the total weight accuracy within +/-15%. This system is used to conduct a long-term monitoring of traffic data. About 2000 ten-wheel trucks, 500 semi-trailers and 500 full trailers are collected. It is found that around 29% of truck traffic carry higher weight than the legal limits. Based on these obtained truck traffic data, the structural safety of the standard slab-type bridges in term of bridge load ratings are evaluated adopting the AASHTO evaluation standard. The obtained load ratings show that the bridges have adequate safety under monitored truck. However, the damage or deterioration of the bridges caused by the heavy trucks can be expected during their design life, especially for the bridges having span lengths of 6-8 m. The fatigue life of the bridges due to the passages of truck traffic is investigated. The induced stress ranges in concrete as well as reinforcement are calculated. Based on the monitored truck weights and volumes, the remaining fatigue life of the standard bridges is found much greater than the design life of 75 years. The useful life of the bridges governed by corrosion is also considered both due to chloride and carbonation. The deterioration models suggested by the NCHRP (2006) and CEB-FIP Model Code (1997) are employed to predict the corrosive deterioration from chloride and carbonation, respectively. Using the data of chloride in actual bridges, the useful life of the bridges close to the shore line is expected to be about 30 years. While the deterioration due to carbonation yields the bridge life of much longer than 75 years. The results obtained from this study are believed to be useful information for bridge designers and owners for their effective design and maintenance planning of the bridges.